Endovascular Thrombectomy With or Without Intravenous Thrombolysis: A Meta-Analysis of Randomized Controlled Trials. Issue 2 (April 2023) - Ishfaq, Muhammad F.; Gulraiz, Sana; Huang, Wei; Lobanova, Iryna; Martin, Renee H.; French, Brandi R.; Siddiq, Farhan; Gurkas, Erdem; Aytac, Emrah; Gomez, Camilo R.; Qureshi, Adnan I.
Background: We performed this meta-analysis of randomized clinical trials to compare the outcomes in patients treated with endovascular thrombectomy who receive prior intravenous thrombolysis with those who do not receive such treatment. Recently, one randomized trial reported outcomes to address this issue, so timely update of meta-analysis is needed to determine the value of administering intravenous thrombolysis before endovascular thrombectomy. Materials and methods: Four randomized clinical trials are included in our meta-analysis. We calculated pooled odds ratios and 95% CIs using random-effects models. The primary efficacy endpoint was a favorable outcome defined by a modified Rankin Scale score of 0 (no symptoms), 1 (no significant disability), or 2 (slight disability) at 90 days post-randomization. Secondary endpoints analyzed were any intracerebral hemorrhage, symptomatic intracerebral hemorrhage, and mortality. Results: Of the 1633 patients randomized, the proportion of patients who achieved a favorable outcome was similar between endovascular thrombectomy alone and combined approach with intravenous thrombolysis and endovascular thrombectomy (1631 patients analyzed; odds ratio 1.02; CI 0.84–1.25; p = 0.83). Risk of any intracerebral hemorrhage was significantly lower among those randomized to endovascular thrombectomy alone (1633 patients analyzed; odds ratio 0.75; CI 0.57–0.99; p = 0.04). Rates of symptomatic intracerebral hemorrhage (p = 0.36) and mortality (p = 0.62) were not significantly different between the two groups. Conclusions: Compared with endovascular thrombectomy preceded by intravenous thrombolysis, endovascular thrombectomy resulted in similar rates of favorable outcome with a lower rate of intracerebral hemorrhage. A large phase 3 trial is required to conclusively demonstrate equivalency of both approaches to guide future practice.